Parody, irony and ideology in the fiction of Ihara Saikaku - Gundry, David J. (Brill's Japanese studies library ;, 2017)
The first monograph published in English on Ihara Saikaku's fiction, David J. Gundry's lucid, compelling study examines the tension reflected in key works by Edo-period Japan's leading writer of 'floating world' literature between the official societal hierarchy dictated by the Tokugawa shogunate's hereditary status-group system and the era's de facto, fluid, wealth-based social hierarchy. The book's nuanced, theoretically engaged explorations of Saikaku's narratives' uses of irony and parody demonstrate how these often function to undermine their own narrators' intermittent moralizing. Gundry also analyzes these texts' depiction of the fleeting pleasures of love, sex, wealth and consumerism as Buddhistic object lessons in the illusory nature of phenomenal reality, the mastery of which leads to a sort of enlightenment.